Land and caste in south India - Dharma Kumar (New Delhi, 1992)
Land and Caste was first published in 1965 by the Cambridge University Press, having been awarded the Ellen MacArthur Prize for the best work in economic history of the year in Cambridge University. It has since established itself as a classic, particu larly for its pioneering analysis of the connections between caste and agricul tural labour, and its novel method of estimating agricultural labour in Madras Presidency at the outset of the nineteenth century, before census data were available. It also brought togeth er a great deal of quantitative informa tion on wages, population and famine, emigration, and other agrarian themes. Although it is essential reading for modern Indian history, and is of great interest to social anthropologists, development economists and others, it has long been out of print. This reissue includes a substantial introduction, surveying work that has appeared in the last three decades, and indicating where Land and Caste needs clarifica tion, revision or amplification; and where its fundamental conclusions still stand.
Keywords: Land tenure-South India